Styles of piety : practicing philosophy after the death of God - Buckner, S. Clark (Samuel Clark), 1968-; Statler, Matthew (Perspectives in continental philosophy ;, 2005)
The last half century has seen both attempts to demythologize the idea of God into purely secular forces and the resurgence of the language of 'God' as indispensable to otherwise secular philosophers for describing experience. This volume asks whether 'piety' might be a sort of irreducible human problem.